CHARACTERIZATION OF THE MECHANICAL PROPERTIES OF MACHETE THOUGHT TO BE FROM THE PAJAJARAN ERA - Muhammad Hiban Akmal Johan; Haryadi Haryadi; Sidik Susilo; Hery Tri Waloyo; Ipick Setiawan (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
This study investigates the dugemslot mechanical properties of a Pajajaran-era golok to reveal the traditional metallurgical technology and cultural values embedded within it. The main issue addressed is the absence of scientific data regarding the manufacturing process and mechanical properties of ancient golok, thus this research aims to identify both aspects. The methodology involved Vickers hardness testing and metallographic analysis using an optical microscope, preceded by geometric measurements and specimen preparation through grinding, polishing, etching. The results indicate a graded mechanical property along the blade, with an average hardness of 184.01 HV: 150.13 HV at the upper section, 189.5 HV at the middle, and 212.4 HV at the lower section. Microstructural observations revealed a dominance of ferrite in the upper section, a combination of ferrite and pearlite in the middle, and a dense pearlite structure in the lower section. These findings suggest that the golok was manufactured using a casting technique combined with differential heat treatment, producing graded mechanical properties: ductile at the spine, balanced at the middle, and hard at the cutting edge. This research contributes to a deeper understanding of traditional metallurgical technology in Nusantara and serves as a reference for further studies as well as cultural preservation through scientific approaches.